INFLUENCE OF COMPLEMENTARY SPORT TRAINING DURING THE TRANSITION PERIOD OVER THE REACTION TIME AND COORDINATION FOR FEMALE BASKETBALL PLAYERS - Dan Mihai GHERŢOIU; Cosmin Mihai MOCA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2019)
Introduction. Basketball is a dynamic team sport that involves a pattern of intermittent dynamic and skilled movement activities that are governed by the reaction time and coordination level of the player. Objectives. The aim of this paper was to determine if the use of complementary sport training (tennis) during the transition period influences the reaction time and the coordination coefficient of young female basketball players, measured using the MGM-15 jumping carpet. Materials and Methods. The participants in this study were female basketball players (N = 14), aged from 11 to 12 years that underwent two measurements: the jumping reaction time test and the coordination coefficient test (EVC) using the MGM-15 carpet before and after a transition period. Results. There was a significant difference between the initial and final measurement for both the reaction time and EVC variable. Conclusion. The reaction time and the coordination coefficient were decreased by the transitional period of complementary sport training.